Republic of Korea : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper discusses the fiscal policy in the Korean business cycle, and examines the usefulness of the equations for inflation forecasting at horizons consistent with the Bank of Korea 's inflation-targeting framework. It analyzes the causes and macroeconomic consequences of Korea's dual labor market; discusses the government's reform proposals; and the nonbank financial sector restructuring to date.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet